Perancangan Timbangan Pengemasan Beras Berbasis Mikrokontroler Atmega32 - Ivan Prastya; Rosidi Sukanta (JURNAL TEKNOLOGI INDUSTRI, 2012)
In everyday life we meet a lot of weight, which is a tool to measure the weight of an object, both large and small capacity. Examples of scales that are used in the store rice is a type of mechanical (conventional) where the possibility of error or human judgment error is very large. Therefore, the authors tried to make rice packaging design scales using ATmega32 microcontroller that can help traders of rice with the accuracy of measurements on the device. From the results it can be seen that try uiji average error rate burden amounted to -0.6% means that the tool is quite accurate. An error due to the input offset voltage of 0.7 mV and the noise in the measurement signal conditioning circuit. Keywords: Microcontroller ATmega32, Scales, Rice